Investigation into the surface chemical analysis and luminescent properties of La7O6(BO3)(PO4)2:Dy phosphor - Che, Yi; Zheng, Youkui; Yang, Dan; Fang, Zhenyu; Li, Cheng; Zhu, Jing (Ceramics international, 2020)
The exploitation of high-quality borophosphate-based phosphor products is currently garnering a significant research focus in solid-state light source. The interest is due to its low-cost and environment-friendly synthesis. In this paper, a new La7O6(BO3)(PO4)2 (LBP):Dy phosphor was developed via sintering at 1673 K for 3 h under an air atmosphere. Structural characterization indicates that all of the prepared products are the monoclinic phases with the space group P21/n. A comparison of the surface chemical states of the elemental compositions for the LBP host versus optimal LBP:13%Dy product was conducted via X-ray photoelectron spectroscopy. Optical characterization shows that the Dy-doped products exhibited visible light emissions of Dy3+ from 4F9/2 to 6H15/2, 6H13/2, and 6H11/2 upon exposure to 348 nm near-ultra violet irradiation. The dominant emission (yellow, 576 nm) belongs to the 4F9/2 → 6H13/2 transition. The best Dy content for doping was 13 mol%, and content quenching occurred due to dipole – dipole interaction. The measured decay lifetime and calculated chromatic properties together manifest that the optimal LBP:13%Dy phosphor shows potential as a yellow ingredient in solid-state lighting.